Pre-germination treatments in pitaya (Hylocereus spp.) seeds to attenuate salt stress - Monaliza Costa Carvalho, Sara (Revista Ciência Agronômica, 2021)
Pitaya (Hylocereus undatus and H. costaricensis) is found in the group of exotic fruits and its cultivation inBrazil is expanding, especially in the semi-arid region of the Northeast. In this region, the problems of water quantity andquality usually cause environmental stresses which limit the survival of plants, especially during germination and seedlingestablishment. Thus, the objective was to evaluate the mitigating action of pre-germination treatments in pitaya seeds undersalt stress. The experiment was conducted in a completely randomized design, in a 2 × 6 factorial scheme, corresponding totwo species of pitaya (H. undatus and H. costaricensis) and six pre-germination treatments (T1 = 0.0 MPa (control); T2 = saltstress (-0.4 MPa); T3 = hydropriming + salt stress; T4 = gibberellic acid + salt stress; T5 = salicylic acid + salt stress; T6 =thiamethoxam + salt stress). After 20 days of sowing, germination, germination speed index, shoot length, primary root length,total dry mass, total soluble sugars and total free amino acids were analyzed. H. costaricensis was more tolerant to salinitythan H. undatus. Salicylic acid stimulated the germination and growth of H. undatus, besides increasing the soluble sugarcontent in H. costaricensis. Seed hydropriming attenuated salt stress during germination of H. undatus and favored dry massgain. Gibberellic acid stimulated the germination of H. undatus and the growth of H. undatus and H. costaricensis seedlings, inaddition to increasing the levels of soluble sugars in H. undatus.